2006
DOI: 10.1136/bjo.2006.096230
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological diagnosis of infective keratitis: comparative evaluation of direct microscopy and culture results

Abstract: Aims: To determine the sensitivity, specificity and predictive values of potassium hydroxide (KOH) wet mount, Gram stain, Giemsa stain and Kinyoun's acid-fast stain in the diagnosis of infective keratitis. Methods: A retrospective analysis of all patients with clinically diagnosed infective keratitis presenting between September 1999 and September 2002 was carried out. Corneal scrapes were taken and subjected to direct microscopy and culture. Results: 3298 eyes of 3295 consecutive patients with infective kerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
102
0
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(126 citation statements)
references
References 18 publications
(13 reference statements)
5
102
0
12
Order By: Relevance
“…The identification of H. capsulatum is undoubtedly the most time consuming with cultivation requiring, on average 25 d to develop visible growth. Subsequent identification is micro morphological, confirmatory assay identification (pleomorphism test) may take over 25 d [7,8,18]. An attractive possibility for the use of PCR-RFLP, therefore, consists in the identification of colonies obtained from clinical samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of H. capsulatum is undoubtedly the most time consuming with cultivation requiring, on average 25 d to develop visible growth. Subsequent identification is micro morphological, confirmatory assay identification (pleomorphism test) may take over 25 d [7,8,18]. An attractive possibility for the use of PCR-RFLP, therefore, consists in the identification of colonies obtained from clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…The MALDI-TOF technique is being used as an alternative to precocious identification of fungal species; however, it is still not a reality in Brasil [5,6]. To overcome these limitations, molecular approaches can be used for the detection and identification of pathogenic fungi [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…20 Various studies revealed the utility of KOH preparation in fungal corneal ulcers. 8,18,20,21,22 The sensitivity of KOH preparation has been found to be variable ranging between 33-94% as reported by various studies. The sensitivity and specificity of KOH preparation in our study was 45.45% and 75% respectively.…”
Section: Discussionmentioning
confidence: 94%
“…For various reasons, the positivity of smears is always higher compared with that of cultures. [17][18][19] The sensitivity of KOH preparation has been reported to range from 94.3% to 100%. 8,19,20 These studies recommend that all smear-positive cases of mycotic keratitis be treated accordingly, despite negative culture reports.…”
Section: Discussionmentioning
confidence: 99%